Система комп’ютерного перекладу української жестової мови з використанням граматично доповненої онтології - Лозинська, Ольга Володимирівна (Національний університет "Львівська політехніка", 2016)
У дисертації розроблено методи та засоби системи комп’ютерного перекладу анотованої української жестової мови з використанням граматично доповненої онтології. Досліджено проблему перекладу анотованої української жестової мови. Вперше побудовано систему правил для перекладу анотованої української жестової мови із використанням граматично доповненої онтології. Удосконалено метод комп’ютерного перекладу на основі правил анотованої української жестової мови з використанням граматично доповненої онтології. Одержав подальший розвиток метод наповнення онтологій з використанням предметно-орієнтованих мов, що дало змогу розробити граматично доповнену онтологію. У результаті розроблено систему комп’ютерного перекладу анотованої української жестової мови, що дало змогу підвищити відсоток правильно перекладених речень української словесної мови на українську жестову до 93,2 % порівняно зі статистичним методом перекладу (57,2 %) та методом перекладу на основі правил (75,3 %). В диссертации разработаны методы и средства системи компьютерного перевода аннотированного украинского жестового языка с использованием грамматически дополненной онтологии. Исследована проблема перевода аннотированного украинского жестового языка. Впервые построена система правил для перевода аннотированного украинского жестового языка с использованием грамматически дополненной онтологии. Усовершенствован метод компьютерного перевода на основе правил аннотированного украинского жестового языка с использованием грамматически дополненной онтологии. Получил дальнейшее развитие метод наполнения онтологий с использованием предметно-ориентированных языков, что позволило разработать грамматически дополненную онтологию. В результате разработана система компьютерного перевода аннотированного украинского жестового языка, что позволило повысить процент правильно переведенных предложений украинского словесного языка на украинский жестовый язык до 93,2 % по сравнению со статистическим методом перевода (57,2 %) и методом перевода на основе правил (75,3 %). In the thesis an important scientific task of developing computer and linguistic methods and means for computer translation of annotated Ukrainian sign language using grammatically augmented ontology was resolved. The problem of developing a machine translation system for sign language has been studied by scientists for a long time. The solution to this problem can provide new communication opportunities for people with hearing impairments. The challenge of translation from Ukrainian sign language (USL) to Ukrainian spoken language (USpL) refers to tasks of machine translation. Author performed the original research of the linguistic peculiarities of Ukrainian sign language and developed the grammatically augmented ontology (GAO) of Ukrainian spoken language and Ukrainian sign language. The mathematical model of grammatically augmented ontology was developed. The model provides the possibility of integrating expressions into ontologies and supports the means for description of grammatical attributes. Author developed software and algorithmic complex for bidirectional translation Ukrainian sign language. Method and algorithm for machine translation annotated Ukrainian sign language based on grammatically augmented ontology were developed. The use of the developed grammatically augmented ontology for parsing sentences in Ukrainian spoken and Ukrainian sign languages improved the performance of APCFG parser. The major increase in percentage of correctly parsed sentences was achieved for Ukrainian sign language. The rules of syntax and semantic analysis of USL and USpL sentences based on grammatically augmented ontology were developed. Domain specific language named GAODL for description of grammatically augmented ontology was created. The grammar of the language was defined by means of Xtext framework for Eclipse. This approach lets to use Eclipse environment with intelligent code completion for editing ontology files. The use of GAODL facilitates uniform editing and processing of grammatically augmented ontologies. These ontologies could be created for specific subject areas and lately merged to obtain upper ontologies. The GAODL language contains constructions for definition of new grammatical attributes, synsets, relations on synsets, predicates and expressions. As a result, a computer translation system of annotated Ukrainian sign language using GAO was developed. The quality of Ukrainian sign language translation was increased to 93.2 % compared to the statistical method of translation (57.2 %) and the rule-based method of translation (75.3 %). The main results of the dissertation research implemented in Lviv Maria Pokrova Secondary Residential School for Deaf Children.
Система компьютерного перевода украинского жестового языка с использованием грамматически дополненной онтологии
Computer translation system of Ukrainian sign language using grammatically augmented ontology
Keywords: система комп’ютерного перекладу; українська жестова мова; граматично доповнена онтологія; дерево синтаксичного розбору; афіксна ймовірнісна контекстно-вільна граматика; система компьютерного перевода; украинский жестовый язык; грамматически дополненная онтология; дерево синтаксического разбора; аффиксная вероятностная контекстно-свободная грамматика; computer translation system; Ukrainian sign language; grammatically augmented ontology; parsing trees; affix probabilistic context free grammar